Studi Komparasi Strategi STAD (Student Teams Achievement Division) dengan Strategi Make a Match terhadap Hasil Belajar IPA Siswa Kelas 3 di SD N Gemolong 2 Tahun 2015/ 2016 - Octavia, Leyla Ary (2016)
This research has a purpose: (1) different effect between STAD strategy and Make a Match strategy to the learning achievement on IPA subjects at the third grade student of SD N Gemolong 2 Year 2015/2016. (2) greater influencebetween STAD strategy and Make a Match strategy to the learning achievement on IPA subjects at the third grade student of SD N Gemolong 2 Year 2015/2016. This studyincludeda quantitative study with an experimental model, the research subjectis class 3A and 3 B SD N Gemolong2. The data collection techniqueusing the techniques oftests and documentation. Testing instruments used validity and reliability. Data analysis technique using t-test technique which preceded the prerequisite test analysis is the normality and homogeneity test. Based on data analysis with a significance level of 5% tobs > ttable = 3.611 and 3.618 > 2.01954. Andobtained a meangrade of classes taught using STAD strategy and classes taught using theMake a Match strategy is 85.68 > 77.62. The conclusion fromthis study is: (1) There is a difference effect between STAD strategy and Make a Match to the learning achievement on IPA subjects at the third grade student of SD N Gemolong 2 Year 2015/2016. (2) STAD strategy greater influence than the Make a Match strategy to the learning achievement on IPA subjects at the third grade student of SD N Gemolong 2 Year 2015/2016.